Palmoplantar pustulosis with psoriatic arthritis ineffective to interleukin-17 inhibitors: two patients successfully treated with upadacitinib - Zeng-; Wen-Yao Mi; Yi-Yi Wang; Wei Li (Taylor & Francis Group, 2023)
AbstractPalmoplantar pustulosis (PPP) is a rare chronic pustular disease. Psoriatic arthritis (PsA) is one of the common manifestations of arthritis in PPP associated with a high burden of disease. The treatment of PPP is difficult and still in the exploratory stage. Only a few cases show that PPP complicated with arthritis have been successfully treated with janus kinase inhibition, interleukin (IL)-6 inhibitors, IL-12/23 inhibitors and tumor necrosis factor inhibitors. Here we reported that two patients were diagnosed as PPP with PsA and initially treated with IL-17 inhibitors. One case was only partially relieved, and the other case had severe paradoxical reaction in the trunk. The joint and skin condition of two patients had been significantly improved without reported adverse reactions after 18 weeks treatment with upadacitinib, which support upadacitinib may be a potential option for patients with PPP combined PsA.